Use of the capping agent for the electrochemical detection and quantification of nanoparticles: CdSe quantum dots - Hepburn, W; Batchelor-McAuley, C; Tschulik, K; Kachoosangi, R; Ness, D; Compton, R (2014)
The electrochemical detection of organic capped CdSe nanoparticles is achieved down to the highly dilute concentration of 15 pM. Herein, electrode modification is undertaken either via a simple and fast adsorption methodology, or by direct dropcasting of the material. Importantly, the adsorption of the CdSe nanoparticles is evidenced at higher surface coverages by the direct measurement of the cadmium reduction signal. A lower analytical detection limit for the CdSe nanoparticles is enabled by the enhancement of the diffusional borax reduction signal on a gold electrode modified with the quantum dots. The presence of a non-electroactive layer on an electrode has been shown to alter the apparent electrochemical rate constant via modifying the solubility and mass-transport of an electroactive species adjacent to the electrochemical interface. In the present case the origin of the enhanced rate of reduction for borax is ascribed as being due to the presence of the non-electroactive organic capping agent. Hence, due to the ubiquitous nature of capping agents within the field of nano-chemistry, the methodology represents a facile and generally applicable detection route. © 2014 Elsevier B.V.